PENGARUH NET PROFITABILITAS TERHADAP HARGA SAHAM PADA SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE TAHUN 2013 – 2017 - Putri Sarirati; Ervina Oktaviani (Sekolah Tinggi Manajemen IMMI Jakarta, 2022)
This study investigates the interrelationships between return on assets, return on equity and earnings per share on stock prices in construction and building sub-sector companies listed on the Indonesia Stock Exchange over the period 2003–2017. In this study, multiple linear regression analysis was not carried out manually by using a formula but by using Statistical Product Service Solutions (SPSS). The researcher will use data analysis techniques that have been available. First, the data quality test is carried out in the form of validity and reliability tests. Second, the classical assumption test was carried out in the form of normality test, multicollinearity test and heteroscedasticity test. Third, test the hypothesis in the form of F test (simultaneous test), coefficient of determination and t test (partial test). Simultaneously, the return on assets, return on equity and earnings per share variables have a significant effect on stock prices. Partially return on assets and earning per share has a significant effect on stock prices. But return on equity has no significant effect on stock prices.